Global variation in human tooth crown and root morphology - anthropological and forensic applications - 2 - Scott, G. Richard (Henry Stewart Talks, 2018)
Evolutionary mechanisms underlying variation in dental morphology, Dental morphology and population history, Using combination of traits to identify ancestry of individuals in a forensic context